Mandibular Ameloblastoma in an Elderly Patient: A Case Report. (6th March 2013) - Nagata, Kokoro; Shimizu, Kasumi; Sato, Chu; Morita, Hiroshi; Watanabe, Yoshihiro; Tagawa, Toshiro
Abstract : Ameloblastomas frequently occur in relatively young people, but are rarely seen in people aged 80 years or older. We report a case of mandibular ameloblastoma in an elderly patient with a review of the literature. The patient was a 82-year-old man who noticed swelling of the gingiva approximately 2 weeks prior to his initial visit. Computed tomography showed a radiolucent area with little radiopacity. Internal uniformity was observed at the site, with thinning of cortical bone which lacked continuity in some areas. The excision and curettage were performed under general anaesthesia. No recurrence has been observed 14 months after surgery.